Unusual case of pancreatic mucinous cystic neoplasia in a pregnant woman Ungewöhnlicher Fall einer muzinösen zystischen Neoplasie des Pankreasschwanzes bei einer schwangeren Frau - Veits, L.; Deuerling, J.; Henneking, K.; Falkeis, C.; Sterlacci, W.; Vieth, M. (Endoskopie heute, 2015)
A 28 year old pregnant woman presented with acute pancreatitis at our emergency department. Emergency sonography of the abdomen showed a multicystic tumour in the pancreatic tail with in parts prominent septa as reason for the acute obstructive pancreatitis. Subsequently, the lesion was punctured transcutanously with obtaining of fine needle cytology which supported the suspected diagnosis of mucinous cystic neoplasm. Due to low cellularity and scant amount of diagnostic material in the cytological specimen which did not allow exclusion of higher grade dysplasia and because of the early stage of pregnancy, contemporary surgical therapy was considered best and pancreatic tail resection was performed. The final pathological report confirmed the cytological diagnosis.
CRIS-Team Scopus Importer:2025-03-05
Keywords: mucinous cystic neoplasia; pancreas; pancreatitis; pregnancy